Carbono almacenado en las especies de un bosque de terraza baja del distrito del Napo, Loreto.2023 - Cardenas Amasifuen, Linda Maela (2024)
The low terrace forest of the Napo district was examined to determine its carbon storage potential. In the native community of Nueva Libertad, the study was conducted in the cutting plots (PC1) and (PC2) of the intermediate forest management plan for logging permits. Eleven botanical families, twelve commercial forest species and a total of 1023 trees were identified. The dry biomass was 11 672.62 kg/ha in total. The two species with the highest biomass were Maquira coriacea (8305.89 kg/ha) and Calycophyllum spruceanum (1 565.68 kg/ha). They stored 5.836 tC of carbon per hectare. Maquira coriacea (4.15 tC/ha) and Calycophyllum spruceanum (0.78 tC/ha) were the species that stored the most carbon. The results of the Kruskal-Walis test show that there are variations among species in the mean carbon stock. Since there are no significant differences between species groups and the chi-square value is 20.399 and the asymptotic significance is 0.040, both below the 0.05 significance level, there is sufficient data to reject the null hypothesis